DEVELOPMENT OF GAMIFICATION-BASED DIGITAL FLIPBOOK MEDIA ON IPAS MATERIAL (STUDY ON GRADE IV ELEMENTARY SCHOOL) - Bayat, Palgunadi Abdulah; Nusantara, Toto; Suciptaningsih, Oktaviani Adhi (International Education Trend Issues, 2023)
The purpose of this research and development is to produce media products that are valid, complete, practical, and attractive. This research was tested at SD Negeri Balearjosari 1 guided by the ADDIE model to develop digital flipbook media. The data collection techniques used to develop batumema multimedia are tests, observation, documentation, interviews, and questionnaires. The results of this study are in the form of digital flipbook media by utilizing technological developments based on gamification, the media developed can be said to be valid, complete, practical, and interesting, this is evident from the results of data analysis, namely (1) the results of media validation with a total score of 49 with a percentage calculation obtaining 87.5% including the criteria "Very Valid". The results of the material validation obtained a total score of 39 with a percentage calculation obtained 88.63% including the criteria for "Very Valid" material. (2) the results of the calculation that at the first meeting got a percentage of 81.25% while at the second meeting got a percentage of 87.50%. These results have increased in the results of working on student evaluation questions. (3) The calculation results can be known the level of practicality based on the assessment given by the teacher obtained a score of 30 with a percentage of 93%, percentage is included in the "Very Practical" category (4) The attractiveness of digital flipbook media is obtained from filling out a user response questionnaire. Referring to the data that has been obtained, regarding the results of user responses given by student assessments, the total percentage obtained is 86.75%, and the total percentage obtained is in the "Very Good / Very Interesting category. Digital flipbook media on the theme of Indonesia Rich in Culture needs to be developed even better. as for suggestions that need to be considered, the media display should be made more attractive.